2014
DOI: 10.2147/ijn.s68685
|View full text |Cite
|
Sign up to set email alerts
|

Overendocytosis of gold nanoparticles increases autophagy and apoptosis in hypoxic human renal proximal tubular cells

Abstract: Background Gold nanoparticles (GNPs) can potentially be used in biomedical fields ranging from therapeutics to diagnostics, and their use will result in increased human exposure. Many studies have demonstrated that GNPs can be deposited in the kidneys, particularly in renal tubular epithelial cells. Chronic hypoxic is inevitable in chronic kidney diseases, and it results in renal tubular epithelial cells that are susceptible to different types of injuries. However, the understanding of the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 54 publications
3
51
0
Order By: Relevance
“…51 Contrary to the role of autophagy triggered by most nanomaterials, our recently reported studies have revealed that autophagy initiated by AgNPs or/and radiation mediates cytoprotective effect, which is believed to serve as a pro-survival process of cells facing AgNPs and their associated radiation. 49,52 Given that both AuNPs and AgNPs belong to the noble metal nanoparticles, and the roles of their enhanced autophagy are the same, 49,53 this could indicate that autophagy activated by AuNPs plus radiation may be similar in function to that by AgNPs plus radiation. Since protective autophagy antagonizes apoptotic cell death induced by cancer chemotherapy and radiation therapy, 54,55 pharmacological inhibition of this type of autophagy should enhance the anticancer activity of AuNPs alone, AgNPs alone, or their combination with radiation, in particular that of AgNPs-based treatment.…”
Section: Promotion Of Autophagy By Aunps or Agnps In Combination Withmentioning
confidence: 99%
“…51 Contrary to the role of autophagy triggered by most nanomaterials, our recently reported studies have revealed that autophagy initiated by AgNPs or/and radiation mediates cytoprotective effect, which is believed to serve as a pro-survival process of cells facing AgNPs and their associated radiation. 49,52 Given that both AuNPs and AgNPs belong to the noble metal nanoparticles, and the roles of their enhanced autophagy are the same, 49,53 this could indicate that autophagy activated by AuNPs plus radiation may be similar in function to that by AgNPs plus radiation. Since protective autophagy antagonizes apoptotic cell death induced by cancer chemotherapy and radiation therapy, 54,55 pharmacological inhibition of this type of autophagy should enhance the anticancer activity of AuNPs alone, AgNPs alone, or their combination with radiation, in particular that of AgNPs-based treatment.…”
Section: Promotion Of Autophagy By Aunps or Agnps In Combination Withmentioning
confidence: 99%
“…The kidney is an organ with rich and diverse endothelial cells (Verma and Molitoris, 2015). Ding et al found that gold nanoparticles could induce autophagy of hypoxic human proximal tubule epithelial (HK-2) cells (Ding et al, 2014). The basal autophagy in the kidney is vital for the normal homeostasis of proximal tubules, but abnormal autophagy can impair renal function and increased p62 levels and oxidative stress (Kaushal and Shah, 2016;Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrated that treatment with CuNCs significantly decreased the mitochondrial membrane potential in C2C12 myoblasts. Similar results were obtained by Karlsson and coworkers, who suggested that exposure to CuO nanoparticles can cause mitochondrial depolarization (Ding et al ., ; Karlsson et al ., ).…”
Section: Discussionmentioning
confidence: 97%